Boas práticas para o desenvolvimento de jogos de cartas colecionáveis - Paiva, Felipe Gomes Rufino Moura (2017)
Considering the recent increase in the number of generic Collectible Card Games and the lack of guide materials for the development of games of this genre, a grouping of good practices for the development of games of the segment was carried out. This survey was based on academic and non-academic papers on the subject, questionnaires applied with players of the genre and interviews with players, narrators and organizers of official competitions, adding and changing the listing at the end of each point whenever necessary. Through this work, a considerable number of good practices can be raised to be used in the development and improvement of CCGs.